2021
DOI: 10.1038/s41467-021-23933-z
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz response of monolayer and few-layer WTe2 at the nanoscale

Abstract: Tungsten ditelluride (WTe2) is an atomically layered transition metal dichalcogenide whose physical properties change systematically from monolayer to bilayer and few-layer versions. In this report, we use apertureless scattering-type near-field optical microscopy operating at Terahertz (THz) frequencies and cryogenic temperatures to study the distinct THz range electromagnetic responses of mono-, bi- and trilayer WTe2 in the same multi-terraced micro-crystal. THz nano-images of monolayer terraces uncovered we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 51 publications
2
39
1
Order By: Relevance
“…For background-free imaging, the signal amplitudes s n of the scattered radiation are additionally demodulated at harmonics n of the tapping frequency. We found that, in contrast to the terahertz and mid-infrared ranges, , n ≥ 4 is required for the visible and near-infrared spectral range in most experiments. For s -polarized light, the signal-to-noise ratio is decreased due to a weaker coupling to the evanescent fields at the tip apex.…”
Section: Methodsmentioning
confidence: 85%
“…For background-free imaging, the signal amplitudes s n of the scattered radiation are additionally demodulated at harmonics n of the tapping frequency. We found that, in contrast to the terahertz and mid-infrared ranges, , n ≥ 4 is required for the visible and near-infrared spectral range in most experiments. For s -polarized light, the signal-to-noise ratio is decreased due to a weaker coupling to the evanescent fields at the tip apex.…”
Section: Methodsmentioning
confidence: 85%
“…Nanosheets, microcrystals of WTe 2 have been successfully studied for broad spectral/terahertz photodetection 7 , 15 . Compared to nanostructures, thin films of WTe 2 are better for technological applications due to less complexity in device fabrication but the optoelectronics properties of sputtered WTe 2 thin films and their nanoscale active area dependent photodetection remain relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In the future it would be extremely interesting to extend this approach to include more complex heterostructures which feature multiple types material [65,66] including metals [67], insulators [68], superconductors [69,70], ferroelectrics [41][42][43][44][45], magnets [71][72][73][74][75][76][77], and multiferroics [78]-all of which are phases of matter which can be characterized by their couplings to electromagnetic fields and which are now realizeable down to the twodimensional limit [79]. In the future it would be very interesting to consider the mutual coupling of different stacked phases through their shared quantum electrodynamic environment.…”
Section: Discussionmentioning
confidence: 99%